2018
DOI: 10.18632/oncotarget.24666
|View full text |Cite
|
Sign up to set email alerts
|

Findings of multiple HPV genotypes in cervical carcinoma are associated with poor cancer-specific survival in a Swedish cohort of cervical cancer primarily treated with radiotherapy

Abstract: Cervical cancer (CC) is one of the most common cancers in women and virtually all cases of CC are a result of a persistent infection of human papillomavirus (HPV). For disease detected in early stages there is curing treatment but when diagnosed late with recurring disease and metastasis there are limited possibilities. Here we evaluate HPV impact on treatment resistance and metastatic disease progression.Prevalence and distribution of HPV genotypes and HPV16 variants in a Swedish CC patient cohort (n=209) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…To date, this method has only been used on cervical samples. [22][23][24] To the best of our knowledge, only 1 study has evaluated the Anyplex on FFPE samples but it included very few OPSCC cases. 25 In this context, we evaluated the performance of the Anyplex in detecting and genotyping HPV-DNA on a large series of FFPE OPSCCs.…”
mentioning
confidence: 99%
“…To date, this method has only been used on cervical samples. [22][23][24] To the best of our knowledge, only 1 study has evaluated the Anyplex on FFPE samples but it included very few OPSCC cases. 25 In this context, we evaluated the performance of the Anyplex in detecting and genotyping HPV-DNA on a large series of FFPE OPSCCs.…”
mentioning
confidence: 99%
“…Among the numerous subtypes of this virus, the most common and important high-risk type is HPV16. At least 50% of cervical cancers are associated with HPV16 [28]. HPV16 E6 protein is one of the major proteins regulating the life cycle of the virus and plays an important role in tumor cell development.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the most common HR HPV detected in carcinoma cases are HPV 16, 18, 31, 33, 39, and 45 (Muñoz 2000;Kraus et al, 2006;Parkin et al, 2008;Wohlmeister et al, 2016a). Kaliff et al, ( 2018) carried out a study and found that HPV 16 was the most prevalent genotype, followed by HPV 18: the two are the main genotypes detected in squamous cell carcinoma (Oliveira-Silva et al, 2011;Wohlmeister et al, 2016). The 12 other high-risk HPV genotypes (viz.,HPV 31,33,35,39,45,51,52,56,58,59,66,and 68) were highly prevalent in the present study; more in fact than HPV 16 or HPV 18.…”
Section: Discussionmentioning
confidence: 99%